Legal Accountability in Cases of Financial Report Manipulation in Business Entities - Anak Agung Gde Agung Asmara Putra (jurnal.unprimdn.ac.id, 2026)
Financial statement manipulation within the corporate environment is a crucial issue in the modern corporate legal system, impacting corporate integrity and market confidence. This study aims to analyze the forms and modes of financial statement manipulation in Indonesia and internationally, examine the application of fiduciary duty and good corporate governance (GCG) principles in preventing it, and explain the legal consequences and impact of manipulation on minority shareholders, investors, and other stakeholders. The research method used is normative with a legislative, conceptual, and case study approach. The results reveal various modes of manipulation such as revenue overstatement, understatement of liabilities, dummy transactions, and window dressing, which are detrimental to the economy and give rise to criminal, civil, and administrative legal consequences. The implementation of fiduciary duty and GCG has proven effective as a preventive measure to maintain transparency and accountability in financial statements. Financial statement manipulation not only harms investors and minority shareholders but also undermines corporate credibility and capital market stability. Therefore, strengthening internal oversight, audit committees, and strict law enforcement are essential to prevent manipulation practices and maintain public trust.